Development of Social Media–Based Science Educational Content to Train Students’ Digital Literacy using ADDIE Model - Rahman, Ranu A.; Dewi, Novi R. (Jurnal Akademika Kimia, 2025)
This study aims to develop science educational content based on social media to enhance students' digital literacy. The development method used is the ADDIE model, which consists of the stages of Analysis, Design, Development, Implementation, and Evaluation. The subjects of this research were the students of class VIII D at SMP N 41 Semarang. The results showed that the developed science educational content met the criteria of feasibility and practicality based on expert validation, teacher responses, and student feedback. In addition, using social media as a platform for delivering educational content has been proven to enhance students' learning motivation and digital literacy skills. This research implies that science educational content based on social media can serve as an innovative alternative to learning and contribute to improving students' digital literacy.